Use of two functional monomers for a new approach to the synthesis of a magnetic molecularly imprinted polymer for ciprofloxacin - Silva, Lucas M. [UNESP]; Foguel, Marcos V.; Sotomayor, Maria del Pilar T. [UNESP] (Elsevier, 2021)
Ciprofloxacin is an antibiotic widely used in the treatment of human and animal diseases and can be found as a contaminant in some foods of animal origin, such as milk. Thus, the use of molecularly imprinted polymers based on magnetic nanoparticles (mag-MIP) has interesting advantages for extraction in complex samples. Mag-MIP selectivity is provided by careful selection of the functional monomer that will interact with specific groups of the model molecule. Thus, this work presents, for the first time, the performance comparison of mag-MIPs for ciprofloxacin that were synthesized using one functional monomer (mag-MIP1) the acrylic acid, as well as two functional monomers (mag-MIP2), using acrylic acid and 1-vinylimidazole. Both polymers were characterized using different techniques, and the conditions for rebinding the analyte to specific cavities were optimized. Mag-MIP2 showed faster rewiring of ciprofloxacin to polymeric cavities (30 min versus 120 min for mag-MIP1) and better selectivity. Both magnetic polymers were applied to samples of whole and skimmed milk and showed that the percentage range of ciprofloxacin adsorbed to mag-MIP1 was 47–98%, while that for mag-MIP2 was 87–99%. Therefore, mag-MIP synthesized with two functional monomers (mag-MIP2) showed a more promising performance to be applied in the extraction of ciprofloxacin in complex matrices, such as milk.
Keywords: Ciprofloxacin; Functional monomer; Hybrid materials; Magnetic nanoparticles; Molecularly imprinted polymers